The legend of the glorious adventures of Tyl Ulenspiegel in the land of Flanders & elsewhere - De Coster, Charles; Delstanche, Albert (London : Chatto § Windus, 1918)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Tijl Uilenspiegel; legenden; folklore